Analisis Literatur mengenai Implementasi SAK EMKM dalam Penyusunan Laporan Keuangan Persekutuan - Adwitia Dian Savitri; Tesa Br Simbolon; Septi Yulia Ratih; Nadia Mayluna; Endang Kartini Panggiarti (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2026)
This literature review examines the implementation of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in the preparation of financial statements for partnership entities. The study aims to analyze the application of SAK EMKM, identify challenges encountered during its implementation, and evaluate its benefits in improving the quality of financial reporting. This research employs a qualitative approach through a literature review method by collecting and analyzing relevant journals, books, articles, and previous studies related to SAK EMKM and partnership accounting. The findings indicate that the implementation of SAK EMKM contributes positively to the preparation of more structured, transparent, and reliable financial statements. The standard assists business entities in preparing statements of financial position and income statements in a systematic manner, thereby supporting managerial decision-making. However, its implementation remains constrained by limited accounting knowledge, inadequate human resources, and insufficient training and assistance for business owners. The review also reveals variations in the level of SAK EMKM adoption among business entities, influenced by financial management capabilities, educational background, and access to accounting education. Overall, the implementation of SAK EMKM has the potential to enhance financial reporting quality, accountability, and business sustainability, particularly in partnership entities.